Anti-nociceptive activity of stigmasterol on acetic acid-induced inflammation on mice - Haris, Muhammad Ariff (2017)
Stigmasterol is a phytosterol found in many plants such as Tridax procumbens and Tridax procumbens. Based on previous studies, stigmasterol-containing plant extract exhibit hypoglycemic, antioxidant and anti-inflammatory activity, but few studies were carried out on is anti-inflammatory activity as a pure compound. This study investigates the antinociceptive activity of stigmasterol using acetic acid-induced writhing test as the inflammatory pain model. Oral administration of stigmasterol (10, 20, 40 mg/kg) showed antinociceptive ability in a dose-dependent manner. Using indomethacin (10 mg/kg) as standard drug reference, stigmasterol (40 mg/kg) showed significant pain inhibition at min-30, as compared to min-5 (p=0.000). Indomethacin (10 mg/kg) showed a similar pattern to stigmasterol ( 40 mg/kg) and has significant increase in analgesic effect at min- 30, as compared to min-5 (p=0.000). Hence suggesting comparable potency between stigmasterol ( 40 mg/kg) and indomethacin (10 mg/kg). The ability to stigmasterol to inhibit pain may be due to its ability to inhibit of inflammatory mediators such histamine, serotonin, prostaglandin and bradykinin via arachidonic pathway. In conclusion, stigmasterol possesses potent antinociceptive ability comparable to indomethacin and further studies are warranted to determine its molecular mechanism.